No Retrenchment From Employee Empowerment: Employer Wellness Imperatives and Opportunities Emerging From the COVID-19 Pandemic - Gellert, George A.; Montgomery, Scott; Bridge, Oliver; Gellert, Tess E. (Frontiers in Public Health, 2022)
The impact of two years of the COVID-19 pandemic on the relationship between employers and employees are explored, including changing employee sensibilities with respect to future employment, work-life balance, remote and flexible work, and the great resignation. Lasting work changes induced by the pandemic expand employee empowerment and demand for greater work flexibility. Flexibility no longer provides employers a unique selling point and hiring/retention competitiveness – it has become an expected standard. Evolving workplace expectations are tied to realizations of the value of work within the broader context of employees’ lives, changing business culture across many industries. Demand for increased work/employment individualization and personalization overlaps unprecedented personalization of and power of mobile technologies. Human-centered employee management in the post-COVID-19 era will become imperative, with many opportunities for employers to enable greater impact in employee wellness and health promotion driven by deploying compelling virtual-remote engagement and behavioural change technologies.